Local Translation in Axons: When Membraneless RNP Granules Meet Membrane-Bound Organelles - Pushpalatha, Kavya Vinayan; Besse, Florence (Frontiers in Molecular Biosciences, 2019)
Eukaryotic cell compartmentalization relies on long-known membrane-delimited organelles, as well as on more recently discovered membraneless macromolecular condensates. How these two types of organelles interact to regulate cellular functions is still largely unclear. In this review, we highlight how membraneless ribonucleoprotein (RNP) organelles, enriched in RNAs and associated regulatory proteins, cooperate with membrane-bound organelles for tight spatio-temporal control of gene expression in the axons of neuronal cells. Specifically, we present recent evidence that motile membrane-bound organelles are used as vehicles by RNP cargoes, promoting the long-range transport of mRNA molecules to distal axons. As demonstrated by recent work, membrane-bound organelles also promote local protein synthesis, by serving as platforms for the local translation of mRNAs recruited to their outer surface. Furthermore, dynamic and specific association between RNP cargoes and membrane-bound organelles is mediated by bi-partite adapter molecules that interact with both types of organelles selectively, in a regulated-manner. Maintaining such a dynamic interplay is critical, as alterations in this process are linked to neurodegenerative diseases. Together, emerging studies thus point to the coordination of membrane-bound and membraneless organelles as an organizing principle underlying local cellular responses.